Fetal reduction in multiple pregnancy and asynchronous delivery of second twin - Quispe Prado, José (2024)
Deferred delivery or asynchronous delivery is rare in multiple pregnancies. When thebirth of the first twin occurs before 20-26 weeks, deferred delivery of the second twinis a therapeutic option that allows increasing the gestational age to achieve viability,pulmonary maturity and survival. A clinical case of deferred delivery of the secondtwin is presented, in which the first delivery was at 24+1/7 weeks and the second at34+2/7, prolonging the pregnancy by 73 days and resulting in a preterm newborn of2,150 g.